Anti-ableist pedagogies in higher education: A systems approach - Nieminen, Juuso; Pesonen, Henri (Journal of University Teaching and Learning Practice, 2022)
Disabilities and neurodiversity are dominantly understood as something that challenges higher education rather than something that enriches it: ableist underpinnings characterize higher education despite policies of widened access. While earlier research has explored ideas such as ‘inclusive pedagogies’ and ‘pedagogies of belonging’, these important contributions have downplayed the marginalizing nature of pedagogy itself. In this conceptual study, we argue that non-ableist approaches to teaching are not sufficient in itself. We suggest a conceptual model for anti-ableist pedagogies to promote belonging and to challenge the exclusion and marginalization of disabled students. We have drawn on the ecological systems model by Bronfenbrenner to examine anti-ableist pedagogies as understood through the theory of systemic change. We provide a theory synthesis by drawing on earlier work on disability studies and anti-racist pedagogies: without systematic approaches to unpack and challenge the idea of a ‘normal, able student’ in pedagogical design and policies, ‘pedagogies of belonging’ fail to foster ‘belonging’ in a system that builds on exclusion. Our study will benefit both practitioners striving for more inclusive higher education as well as researchers aiming to better conceptualize the questions of belonging in the exclusive systems of higher education.